The International Criminal Court: The failure of justice - Marsili, M. (Book of abstracts. Unequal World Conference. Human development in the context of current global challenges, 2020)
The Charter of the Nürnberg Tribunal introduced crimes against peace and crimes against humanity into international criminal law. War crimes, that include grave breaches of the Geneva Conventions and other serious violations of laws and customs applicable in armed conflict, were included upon proposal by the United States in the Rome Statute that establishes the International Criminal Court (ICC). The ICC goes beyond the limits of multilateral international criminal justice which has been applied to the Nüremberg Trials.